The Changes in Revenue and Its Use in Three Low Spending Districts Following Michigan's Finance Reform - Catherine C. Sielke (Educational Considerations, 1998)
While finance reform is an issue in most if not all of the 50 states, Michigan's approach to reform has been somewhat different.